Pengaruh Return On Asset (ROA) Dan Return On Equity (ROE) Terhadap Harga Saham Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) 2021-2023 (Jurnal Riset Manajemen dan Akuntansi, 2025)
In this era of globalization, almost all countries place great importance on the capital market due to its strategic role in strengthening a nation's economic resilience. To buy or sell stocks in the capital market, investors must determine whether a stock is overvalued or undervalued in order to make informed decisions—whether to buy, sell, or hold the stock. This study aims to analyze the effect of Return on Assets (ROA) and Return on Equity (ROE) on stock prices. The research employs a quantitative method. The data used consists of financial statements from banking companies listed on the Indonesia Stock Exchange for the period of 2021 to 2023. The analytical method applied in this study is multiple regression analysis using SPSS version 25. The results indicate that both ROA and ROE do not have a positive and significant effect on stock prices.